Stem torsion in total hip replacement: CT measurements in 60 patients - Sendtner, Ernst (Informa Healthcare, 2010)
BACKGROUND AND PURPOSE: The clinical results of THR may be improved by correct femoral torsion. We evaluated the stem position by postoperative CT examination in 60 patients. METHODS: 60 patients requiring total hip arthroplasty were prospectively enrolled in this study. Minimally invasive THR was performed (anterior approach) in a lateral decubitus position and each patient underwent a postoperative CT examination. The position of the stem was evaluated by an independent external institution. RESULTS: Stem torsion ranged from –19° retrotorsion to 33° antetorsion. Normal antetorsion (i.e 10–15° according to Tönnis) was present in 5 of 60 patients, so the prevalence of abnormal stem antetorsion was 92% (95% CI: 82–97). We found a stem antetorsion outside the range of 0–25° in 21 of 60 hips. Women had a higher mean stem antetorsion (8.0° (SD 11)) than men (1.5° (SD 10)). INTERPRETATION: Postoperative stem antetorsion shows a high variability and is gender-related. We suggest precise assessment of stem antetorsion intraoperatively by means of computer navigation, preparing the femur first. In abnormal stem antetorsion, the cup position can be adjusted using a combined anteversion concept; alternatively, modular femoral components or stems with retroverted or anteverted necks (“retrostem”) could be used.